Wolfpack: o jogo como contributo para a consciencialização da solidão - Belo, Maria Simões (2020)
Starting from the central research question, how can video games contribute to alert and / or report problems of loneliness in society Contemporary, this dissertation addresses issues related to the concepts of game and solitude simultaneously, using available technologies for the conceptualization of a mobile game. Current technologies provide instant connection merging our everyday lives with new challenges, but this connectivity can contribute to increased isolation. Through this research, which takes advantage of a theoretical-practical exploratory methodology, it is found that loneliness originates in several factors, being one of the biggest problems of today's societies. However, we can start to include it in our daily lives as an introspection tool, promoting a more open and consistent dialogue on the subject. Gaming as an interactive medium is ideal for addressing and helping to solve complex themes through mechanics, rules, scenarios and characters, thus introducing relevant topics through play and game. This project shows the potential of ludic systems to promote and generate new dynamics of social awareness. In this context, WolfPack was created, a mobile exploration game where the player will have to learn to manage resources and crack the codes that are scattered throughout the game to break new ground. These features are essential to the gaming experience because what keeps the character alive is the cover that is sustained by the features the player picks up. WolfPack lasts if the player considers appropriate to have a longer journey to understand the game, or even unlock all upgrades that come along the path, all depending on players actions. Each player will thus have a personalized experience, adapting to various playing methods, depending on different strategies, places and even the friendships they create. It was intended to make a project that will create a new community of attentive players, avoiding the isolation of each one of them and society in general. The game prototype was built in Unity with the Playmaker tool. This tool was very important because it allows to develop games without much programming that can incorporate animation, scenarios and even interactive objects. In order to perform the image tests of the character and its relationship with the environments, the character was designed in several steps in order to get different walking cycles, thus perceiving the movement that the character suggests and its connection with the various elements of the playful environment.